A pregnant patient with fetal distress with severe post burn contracture of anterior trunk and perineum: A surgeon's nightmare! - Vathulya, Madhubari (Indian J Plast Surg, 2014)
INTRODUCTION: A case report of a pregnant lady in the third trimester, presenting in the emergency with absent fetal movements is being described. A multi-speciality expertise was involved and a full term female baby was delivered. PRESENTATION: The patient presented in a Government hospital, Dehradun, India. At the time of presentation the fetal heart sounds were absent and subsequently the severe post-burn deformity involving the anterior trunk, perineum and thighs were discovered. MANAGEMENT: Immediately a multi-speciality approach involving the plastic, obstetrics and pediatrics field were called for and an emergency caesarean with simultaneous contracture release with split skin grafts were performed after optimizing the patient for surgery. CONCLUSION: This is one of the first case reports reporting this rare combination of post burn contracture of trunk and perineum with fetal distress requiring emergency caesarean section along with release of abdominal and perineal post-burn contracture. This case interestingly reinforces that in such complicated cases a systematic and a combined multi-speciality approach still holds the key to patient's treatment even in district hospitals.